Colon polyps with early malignancy - Matteucci, Pablo; Pravia, Juan Antonio; Chiossoni, Martha; Cardozo, Tabare (Cirugía del Uruguay, 1971)
Solitary adenomatous polyps of the colon tend to become malignant and the greater their size, the more frequently this occurs; therefore they may be considered precancrous lesions. Their diagnosis is difficult and generally requires exploratory laparatomy which should be complemented by intraoperatory coloscopy. The paper contains an account of the case material of the University Hospital (Hospital de Clínicas), where two cases of adenomatous polyps with malignant transformation "in situ" and one with invasion of the conjunctival stroma, were found a total of six operated cases.